PERANCANGAN SISTEM PENGOLAHAN DATA PENJUALAN CATERING MENGGUNAKAN FUNGSI SUMIFS DAN VLOOKUP EXCEL DI VIN’S KITCHEN - Hayati Fina Setiani; Syafran Nurrahman; Andini Pramestyas; Isma Fuji Arini; Ridwan Ridwan (CV. Denasya Smart Publisher, 2026)
Catering businesses are one type of enterprise that require an accurate and efficient system for managing sales and financial data. Vin’s Kitchen, as a local catering business, still performs manual recording and processing of sales data, which may lead to calculation errors, delays in report preparation, and difficulties in financial data analysis. This study aims to design and analyze a catering sales data processing system based on Microsoft Excel by utilizing the SUMIFS and VLOOKUP functions. The research method used is applied research with a descriptive and case study approach. Data collection techniques include interviews, documentation, observation, and literature study. The results show that the system is able to improve time efficiency by approximately approximately 80% and reduce the error rate by approximately approximately 85%. The SUMIFS function enhances the speed and accuracy of data calculations, while the VLOOKUP function improves data retrieval speed and consistency, making the data processing more effective and integrated. The proposed system can accelerate the preparation of sales reports, minimize recording errors, and facilitate financial data analysis. This study is expected to provide a practical solution for small and medium-scale catering businesses and can be further developed into a larger-scale system.